Techno-economic analysis of onshore and offshore wind farms in Türkiye - Ergişi, Samet (Graduate School, 2023)
In recent years, the global capacity of wind energy has been experiencing a rapid growth, with onshore wind farms accounting for the majority of the growth. As of 2022, the global installed capacity of wind energy reached 906 GW, of which around 93% is onshore and 7% is offshore. China, the United States, and Germany are currently the top three countries in terms of installed wind energy capacity. In Türkiye, the installed capacity of wind energy has also been steadily increasing. As of January 2023, the total installed wind energy capacity in Türkiye is over 11.9 GW. Despite Türkiye being bordered by the sea on three sides, the country is yet to establish an offshore wind farm. However, the Turkish government has set ambitious targets for increasing the share of renewable energy in the country's electricity mix, including a goal of reaching 5 GW of installed offshore wind energy capacity by 2035. In this study, a thorough techno-economic analysis of onshore and offshore wind farms in Türkiye is presented.The study utilizes simulations with different wind turbine models to optimize energy production and calculate key economic metrics such as net present value (NPV), levelized cost of electricity (LCoE), and internal rate of return (IRR). With a specific focus on one onshore and one offshore wind farm location, the research facilitates a comparative assessment of different turbine models to identify the most efficient and cost-effective options for wind energy generation. After conducting a comprehensive analysis and extensive review of relevant literature, the Northern site of Bozcaada Island has been meticulously chosen as the optimal location for the offshore wind farm. Additionally, considering the necessary capacity allocation and technical permits obtained, the Ezine Substation has been identified as the optimal grid connection point for the offshore wind farm. To ensure a fair comparison with the offshore wind farm's distance to the grid connection point, a site between the villages of Derbentbaşı and Çamlıca in Ezine has been selected for the onshore wind farm by taking into consideration the wind atlas of the region. This selection aims to maintain a similar proximity to the grid connection point, allowing for equitable evaluation and comparison of both onshore and offshore wind farm projects. By choosing the Bozcaada Island's Northern site for the offshore wind farm and the Derbentbaşı - Çamlıca area for the onshore wind farm, this study ensures that both projects are located in optimal positions for efficient energy production and effective grid connection. In order to conduct accurate energy yield assessments for both onshore and offshore wind farms, WindFarmer Analyst 1.5.0 software and ERA5 data has been used. WindFarmer Analyst software is a widely used and specialized tool in the field of wind energy analysis. It is a software application that enables detailed assessments and simulations of wind farm projects. Developed by DNV specifically for wind energy professionals. WindFarmer Analyst provides advanced features and functionalities to analyze the performance, feasibility, and economic viability of wind farms. On the other hand, ERA5 is a widely recognized and reliable dataset, provides comprehensive meteorological information necessary for evaluating wind resources and estimating energy production. By utilizing ERA5 data, this study ensures a robust and consistent approach to the energy calculations for both wind farm projects. The utilization of ERA5 data enhances the accuracy and reliability of the energy assessments, enabling a comprehensive analysis of the wind farms' potential energy output. For onshore wind farm, a comprehensive selection of 7 distinct wind turbine models was utilized, representing 4 reputable manufacturers: Enercon, Vestas, Nordex, and GE. This diverse range of turbine models enabled a comprehensive evaluation of their performance and efficiency in maximizing energy production for the onshore wind farm site. In the case of the offshore wind farm, a Siemens Gamesa offshore wind turbine model with two different hub heights were utilized. WindFarmer Analyst software provides conceptual wind turbine models with varying unit power and hub heights. To calculate the annual energy production for the offshore site, three additional conceptual models were incorporated, resulting in a total of five turbines allowing for a comparative assessment of their performance and suitability for the offshore wind farm site. This study also incorporates various sensitivity analysis to further enhance the understanding of the offshore wind farm project. Firstly, sensitivity of wind farms to variations in total installed capacity through different layouts using varying numbers of wind turbines were analysed. The initial study involved a layout with 28 wind turbines for the offhore wind farm. To conduct a sensitivity analysis, four additional layout scenarios were investigated, including configurations with 8, 12, 16, and 20 wind turbines. This allowed for a comprehensive assessment of the sensitivity of the wind farm's performance across different turbine layouts and installed power. In addition, various scenarios were examined, considering different percentages of cost reductions and analyzing financial outcomes under different discount rates. By altering the discount rate, the study provided insights into the financial viability and robustness of the project in different economic scenarios. Furthermore, this study explores the sensitivity of the offshore project with YEKDEM incentive and the revenues from green energy certificates. The analysis expands the understanding of how changes in market conditions and pricing mechanisms can affect the financial outcomes of offshore wind farms. The simulations in this study indicate that onshore wind farms are a feasible and economically viable option in Türkiye, with several turbine models producing favorable results in terms of energy production and economic metrics. However, the same cannot be said for offshore wind farms, as the simulations show that the high costs associated with offshore installations outweigh the potential benefits of increased wind speeds and energy production. But sensitivity analyses reveal that with the possible future reductions in CapEx, and a new amplified YEKDAM tariff in parallel with the current market prices offshore wind farms investment would be feasible. Overall, this study suggests that while onshore wind farms are a viable option for renewable energy production in Türkiye, offshore wind farms are not yet feasible due to the high costs associated with installation and maintenance. The findings of this thesis could provide valuable insights for policymakers, investors, and other stakeholders in the renewable energy sector in Türkiye, as well as contribute to the broader discussion on the feasibility of offshore wind farms in other regions with similar conditions.
Türkiye'deki karasal ve denizüstü rüzgar santrallerinin tekno-ekonomik analizi
Thesis (M.Sc.) -- İstanbul Technical University, Graduate School, 2023
Keywords: Wind energy; Rüzgar enerjisi; Renewable energy; Yenilenebilir enerji